Modelling global material stocks and flows for residential and service sector buildings towards 2050. (1st February 2020) - Deetman, Sebastiaan; Marinova, Sylvia; van der Voet, Ester; van Vuuren, Detlef P.; Edelenbosch, Oreane; Heijungs, Reinout
Abstract: Residential buildings and service sector buildings have an important contribution to climate change, directly via energy use in these buildings and indirectly through construction activities and the production and disposal of buildings materials. In this paper, we introduce a model that looks at total global building stock for 26 regions between 1970 and 2050 and calculates the floor space and building materials both in new buildings and in demolished buildings. For residential buildings, we build upon the work of Marinova et al. (2019, this issue), who used a building material database to come up with scenarios for materials in the residential building stock. This paper adds two things. First, we introduce a new regression-based model for service building floor space, recognizing 4 different types of service-related buildings. Secondly, we use a dynamic stock model, based on lifetime distributions found in literature, to calculate the construction (inflow) and demolition (outflow) of building floor space for both residential and service-related purposes. We combine this with data from the building material database to come up with scenarios for the annual demand for construction materials worldwide as well as an estimation of the availability of waste materials after building demolition towards 2050. The model can thus be used to assess the potential for closing the material cycles in the construction sector, while distinguishing urban and rural areas explicitly. The results show that demand for construction materials will continue to increase in most regions, even in developed countries. Global demand for steel and cement for the building sector is estimated to be 769 Mt/yr and 11.9 Gt/yr respectively, by the end of the modelling period. This represents a respective growth of 31% and 14% compared to today. Drivers behind this are an expected growth of global residential building stock of about 50%, and a growth of about 150% in the building stock for services. Our model projects that by 2050, only 55% of construction-related demand for copper, wood and steel could potentially be covered by recycled building materials. For other materials the availability of scrap may be higher, reaching up to 71% of new demand in the case of aluminium. This means that in most regions urban mining cannot cover the growing demand for construction materials. Highlights: A model on global building stock and construction materials demand was developed. Building stock includes four types of residential and four types of service sector buildings. A dynamic stock model was used to derive inflow and outflow of building materials. Results highlight the growing demand for construction materials towards 2050. Long lifespans of buildings pose a challenge for achieving a circular economy.